Handbook of research on smart computing for renewable energy and agro-engineering - Kharchenko, Valeriy 1938-; Vasant, Pandian 1961- (IGI Global, 2020)
"This book examines the benefits and barriers of implementing computational models to agricultural production and energy sources as well as how these models can produce more cost-effective and sustainable solutions"--
Keywords: Electricity in agriculture / Data processing; Renewable energy sources / Data processing; Remote area power supply systems; Artificial intelligence